Reemployment Incentives for Unemployment Insurance Beneficiaries: Results from the Washington Reemployment Bonus Experiment - Christopher J. O'Leary; Robert G. Spiegelman; Kenneth J. Kline (W.E. Upjohn Institute for Employment Research, 1993)
Unemployment insurance is intended to reduce hardship by providing labor force members with partial wage replacement during periods of involuntary unemployment. However, in performing this income maintenance function, unemployment insurance may prolong spells of unemployment. Evidence from a field experiment conducted in Illinois in 1984 suggested that offering unemployment insurance claimants a modest cash bonus for rapid reemployment would increase the speed of return to work and reduce program costs. In 1988 a similar experiment, examining several different bonus offers, was conducted in Washington State. Evidence from the Washington experiment indicates that bonus offers do change job seeking behavior, but that only relatively generous bonus offers about six times the weekly benefit amount should be expected to significantly change the behavior of persons eligible for unemployment benefits.
Keywords: J6; H5; 330; unemployment; insurance; bonus; experiment; Washington; O'Leary